A Study on Law Students’ Perceptions of the Integration of Legal Terminology in English within ESP Instruction in Higher Education - Bunga Ayu Wulandari; Ahmad Ridha; Robi Soma; Fauzan, Muhammad (FKIP Universitas Jambi, 2025)
The increasing globalization of legal practice requires law students to develop strong command of English legal terminology as a key component of English for Specific Purposes (ESP) learning. This study explores how law students perceive the importance, challenges, and learning strategies related to the integration of English legal terminology in ESP courses at the tertiary level. Using a qualitative descriptive approach with an intrinsic case study design, data were collected from eight law students through semi-structured interviews, participatory classroom observation, and documentation review. The data were analyzed using thematic analysis supported by NVivo software. The findings show that students regard mastery of legal terminology as indispensable for understanding international legal materials, succeeding in law related subjects, and preparing for future international legal practice. However, they encounter substantial challenges, including polysemy, pronunciation difficulties, dense legal texts, and limited instructional time. To cope with these obstacles, students employ various strategies such as using digital lexicons and online resources, engaging in peer discussion, participating in legal role-plays, and repeatedly interacting with authentic legal documents. The study also reveals that the perceived effectiveness of ESP courses is closely tied to lecturer engagement, the use of authentic materials, and curriculum design that aligns assessment with real legal tasks. The findings offer important implications for curriculum developers and lecturers in designing ESP Law programs that foster legal English proficiency, critical thinking, and global legal literacy.